Choosing the proper animal model for oral submucous fibrosis research: considerations and challenges - Zhang, Linlin; Chen, Jun; Li, Fuxingzi; Liu, Binjie; Liu, Junjie (Frontiers in Physiology, 2025)
ObjectivesAnimal models of oral submucous fibrosis (OSF) are essential for the studying on the pathogenesis of this disease. Current research on animal models of OSF requires further investigation. In this review, we aim to summarize the strengths and weaknesses of existing OSF animal models, as well as the recent progress in this field.Subject and methodsOSF is an oral potentially malignant disorder (OPMD) characterized by fibrotic bands, burning sensations, and limited mouth opening. Numerous experimental animal models have been developed to replicate the pathological processes in patients with OSF. Therefore, we systematically evaluated existing animal models of OSF classifying them according to the elements of building an animal model.ResultsIn this study, we propose that the elements of animal models for OSF include inducers, animal species, and methods of intervention. Additionally, we highlighted the advantages and limitations of these models and provided directions for future research.ConclusionUsing human-like animals as experimental subjects, combining both physical and chemical stimulation, and adjusting the dosage and type of inducer may represent the direction of future studies in this field.